INTRODUCTION AND SOSIALIZATION OF INFORMATION TECHNOLOGY FOR EARLY CHILDHOOD EDUCATION - Syarifah Farissi Hamama; Syarifah Fadiya Hallaby; Maulida Maulida; Nurul Nisa (Universitas Muhammadiyah Aceh, 2024)
The development of information technology has a major influence almost on all aspects of life, including education. However, if used unwisely, the information technology can be very detrimental to its users. One of the main reasons is due to the large amount of unfiltered technological media negative contents which are easily accessed. Therefore, it is very important to introduce appropriate information technology for young children. It is also important to teach parent how to guide and supervise their young children in utilizing the information technology. Hence, this community service activity of Introduction and Socialization of Information Technology for Early Childhood Education is conducted. The targeting audiences of this service are students and teachers at Kota Baru Kindergarten, Banda Aceh. This community service activity is funded by Abulyatama University. This activity was attended by 17 participants of teachers and pre-school students. The obtained result evaluation show that the community service activity increases the knowledge of the pre-school student and teachers regarding how to use the information technology safely. This service activity was successfully conducted due to tremendous support from many groups especially the participants, whom were enthusiastic and actively participated in this socialization activity. Keywords: socialization, information technology, learning media, young children,PAUD